Navigating Reversed Valuation Dilemmas: SME Enterprises Nationalized in 1950s Poland - A Case Study - Wyrobek, Joanna Maria; Oleksy, Paweł; Nieścior, Bartosz (Zielona Góra: Faculty of Economics and Management Press)
The publication describes a problem that often arises in court cases regarding the valuation of SME forcibly nationalized in the 1950s. Valuation of compensation to previous SME owners is an ongoing court debate in Poland. The authors proposed an approach that took into account the economic conditions at that time and complied with the principle of paying compensation for the actual losses incurred, and not for the potential losses that could be incurred as a result. At the same time, the publication analysed other similar judgments in cases regarding compensation for nationalized enterprises. The practical and scientific value of the publication lies in the fact that it addresses an existing practical problem and its solution.
Keywords: company valuation; nationalization; compensation calculation